2020
DOI: 10.1080/09537287.2020.1810757
|View full text |Cite
|
Sign up to set email alerts
|

Food supply chain in the era of Industry 4.0: blockchain technology implementation opportunities and impediments from the perspective of people, process, performance, and technology

Abstract: The prevention of food loss throughout the supply chain, including manufacturers, has become a major challenge for a number of organisations. In addition, consumers are also increasingly interested in the authenticity of food and want to ensure that they receive the right quality of food. To address this issue, there is a need for reliable and robust tools to be available in the Industry 4.0 era that can trace the food throughout the supply chain from the farm through processing until it reaches the customer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
207
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(215 citation statements)
references
References 127 publications
1
207
0
7
Order By: Relevance
“…For instance, blockchain technology increases trust, authenticity, and transparency [ 34 ]. However, there are several challenges such as the need for Internet-of-Things devices throughout the food supply chain to capture all the necessary data from several parties (supply chain actors) and transfer the data to the blockchain [ 35 ]. Moreover, blockchain technology is quite new, and long-term impacts of its implementation in the food chain are not yet proven [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, blockchain technology increases trust, authenticity, and transparency [ 34 ]. However, there are several challenges such as the need for Internet-of-Things devices throughout the food supply chain to capture all the necessary data from several parties (supply chain actors) and transfer the data to the blockchain [ 35 ]. Moreover, blockchain technology is quite new, and long-term impacts of its implementation in the food chain are not yet proven [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Step 1. Decomposing the problem into a hierarchy: Bai and Sarkis (2020) Proposed a group decision-making model which integrated hesitant fuzzy sets and regret theory to evaluate transparency and sustainability for blockchain technology Chang et al (2020) Provided an outline of the latest developments in blockchain technology in global SCM from a variety of sources Choi (2020) Studied financing problems within SCs for fashionable products by developing an analytical model for blockchain-supported and conventional SCs Choi et al (2020) Explored product information disclosure on two blockchain-based rental service platforms, applying the Nash game Choi et al (2020b) Explored how blockchain technology can increase the social media analytics utilization for managing supply chain operations Choi et al (2020c) Explored the impacts of customers' risk attitude toward the optimal on-demand service pricing decision by applying the mean-risk theory and identified how the blockchain assists the platform in assessing the proportion of various customers' risk attitudes Dutta et al (2020) Reviewed blockchain literature in relation to supply chain operations and discussed applications, challenges, and future research directions Ghode et al (2020) Prioritized challenges for adoptability of blockchain technology in SCs using gray relational analysis (GRA) and categorized challenges into four groups, i.e., organizational, technological, operational, and social Hastig and Sodhi (2020) Presented business requirements and critical success factors for better utilization of supply chain traceability systems Kayikci et al (2020) Explored the impact of blockchain technology in food supply chains Lohmer et al (2020) Studied resilience in supply chains through blockchain coordination Manupati et al (2020) Applied blockchain technology to monitor SC performance and optimize emissions and operational costs Pournader et al (2020) Conducted a systematic literature review and identified four major clusters in blockchain literature Rahmanzadeh et al (2020) Applied a fuzzy mathematical model within a blockchain platform to optimize tactical decisions regarding SC objectives and open innovations Wamba and Queiroz (2020) Proposed a three-stage model of blockchain adoption in supply chains Wong et al (2020) Studied the behavioral aspect of blockchain technology adoption in supply chain management Yoon et al (2020) Studied the impact of blockchain technology implementation on firms' exporting performance Azzi et al (2019) Explored how SCs can benefit from blockchains by creating a transparent, reliable, and secure system Biswas and Gupta (2019) Investigated obstacles to blockchain technology adoption and implementati...…”
Section: The N-ahp Proceduresmentioning
confidence: 99%
“…According to [85], trust, security, and transparency in Wal-Mart's food supply chain increased thanks to the adoption of blockchain technology, which requires parties who access blockchain to present documents and register data. Subsequently, food waste can be controlled, and the chance of corruption and risk of food fraud can be minimized significantly [86,87].…”
Section: Cluster 3: Traceability Database Systems To Ensure Food Safementioning
confidence: 99%